PSYCHOLOGICAL BIASES IN INVESTMENT DECISIONS: AN EXPERIMENTAL STUDY OF MYOPIC BEHAVIOR IN DEVELOPING CAPITAL MARKETS - Wendy, Wendy; Asri, Marwan (Journal of Indonesian Economy and Business, 2012)
This paper attempts to analyze the psychological biases that affect investors in making risky investment decisions based on the theory of Myopic Loss Aversion (MLA). The datawere obtained from two sources (students and stock investors) which in turn were manipulated by two types of treatment (frequent and infrequent), using a mixed design of betweenwithin subjects with a 2 x 2 factorial. The experimental result showed the consistency of the two groups of participants to the theory of the MLA. Analysis of the gender showed that the boldness levels of the male participants and female participants in the group of investors were the same, while in the student group, gender showed a significant influence. Other findings included a